Speculative communities living with uncertainty in a financialized world - Komporozos-Athanasiou, Aris (The University of Chicago, 2022)
"In Speculative Communities, Komporozos-Athanasiou examines the ways that financial speculation has moved beyond markets to shape fundamental aspects of our social and political lives. As ordinary people make exceptional decisions--such as the American election of a populist demagogue or the British vote to leave the European Union--they are moving from time-honored and -tested practices of governance, toward the speculative promise of a different kind of future. Even our methods of building community have shifted to the speculative realm as social media platforms enable and amplify alternative visions of the present and future-these are the "speculative communities" that now shape our personal and political realities. For Komporozos-Athanasiou, "to speculate" means increasingly "to connect," to endorse uncertainty preemptively, and often daringly, as a means of social survival. Finance has thus become the model for society writ large. These financial systems have taken a notable turn in our current era, however. Contemporary capitalism sees the risk-taking, entrepreneurial person being refashioned as a politically disoriented, speculative subject, who embraces the future's radical uncertainty rather than averting it. As Komporozos-Athanasiou shows, virtual marketplaces, new social media, and dating apps function as finance's speculative infrastructures, leading to a new type of imagination across economy and society"--